Preventing Violence and Harassment Through Leadership, Policy, and Safety Culture in Emergency Healthcare Settings - Arjun Bhandari Thapa; Pratiksha Priya Shakya (Safety and Health for Medical Workers, 2025)
Objective: This article investigates the effects of leadership commitment, organizational policies, training, reporting mechanisms, and workplace culture in reducing harassment and violence in work organizations.Methods: Quantitative cross-sectional survey design of employees in various industries. Responses were analyzed by structural equation modeling to investigate direct and indirect relationships between factors. Findings: The findings indicate that leadership support, sound policy implementation, and strong response are effective in minimizing workplace harassment and violence. Training and education programs develop the resiliency and awareness of employees to inappropriate behaviors. What’s more, a supportive organizational culture is a powerful driver in preventing misbehavior and suggests that societal approaches are more effective when they’re combined instead of working in isolation. Novelty: This study adds to the literature by combining several organizational-level initiatives as part of one comprehensive framework, creating a comprehensive view of how structural and cultural interventions intersect to reduce workplace harassment. Unlike past research concentrating on single variables, the present work highlights how leadership, policy, and culture act as additive mechanisms. Research Implications: The results have implications for the necessity of taking a multi-level and systems-oriented perspective to organizational governance. Policy makers and managers are recommended to integrate harassment-prevention measures into broader cultural change efforts for an impact that lasts. This analysis also has implications for international labor standards in a practical sense, as it offers evidence-based guidance to organizations within different cultural and legal frameworks.